Building the Workforce Behind the Wheels: HR Practices in the Automotive Dealership Sector - Aneesha Aneesha Madur (Garuda Prestasi Nusantara Consulting, 2026)
The automotive dealership sector is a people-intensive industry in which organizational performance depends not only on vehicles, technology, sales and customer service, but also on the effectiveness of its workforce. Human Resource Management (HRM) therefore plays a critical role in attracting suitable talent, maintaining employee information, supporting workforce administration and creating a positive work environment. This article examines important HR practices relevant to the automotive dealership sector, with emphasis on recruitment and selection, digital talent sourcing, resume screening, interview coordination, onboarding, employee documentation, attendance administration, HR technology, campus recruitment, reference verification and employee engagement. The discussion is based on HR activities documented across four fortnightly organizational-training reports and is presented in an analytical rather than personal-experience format. The article highlights how people management, structured processes, digital tools and accurate HR data work together to support effective workforce management.